Application to support learning android based in SMPN 18 surakarta - Alfonsa Maria Sofia Hapsari; Tigus Juni Betri; Dyka Nasution (RESEARCH FAIR UNISRI, 2021)
Based program android is useful for teachers as any media learning that can be used to given the lectures to students , especially in the hamper now where all students having android phone. This pandemic in the , online learning is the only alternative given the lectures to students and android based program was very helpful in learning . This study attempts to know whether application to support learning android based in SMPN 18 Surakarta .Study was conducted the survey with spread after teachers try to use application android based this. The results of the study said 43 % said application support learning and 57 % is very conducive to learning